أثر السياق التداولي فى توجيه الدلالة: الخطاب القصصي القرآني نموذجاً - براهيمي، الحاج (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست - معهد الآداب واللغات, 2019)
تناولت المقالة أثر السياق في توجيه الدلالة في الخطاب القصصي القرآني، واختارت سورة الكهف نموذجا للتحليل، وذلك على عدة مستويات، منها المستوى الصوتي والمعجمي والتركيبي، ويتجلى المستوى الأخير (التركيبي) في مظاهر عدة: بيان التقدم والتأخير وأثره، بيان الحذف وتقديره، وتحديد مرجع الضمير، فضلا عن مظاهر نحوية وبلاغية أخرى ينبئ عنها التحليل السياقي التداولي، وقد خلص البحث إلى ضرورة استثمار السياق وعدم إغفاله في تفسير القرآن، وتحليل الخطابات من قبل الدارسين، لأنه يشي بحقيقة مقاصد الخطاب الشرعي خاصة، والخطاب بصفة عامة.
The article discussed the contextual impact of directing the significance in the Qur'anic narrative discourse. Sourat Al-Kahf is chosen as model for analysis at several levels, including the level of phonetic, lexicon and syntactic, The last level (syntactic) is manifested in several aspects: the presentation of the delay and its effect, the statement of the deletion and its estimation, and the determination of the reference to the conscience, The research concluded that the context should be exploited and not overlooked in the interpretation of the Qur'an, and the analysis of the speeches by the researchers, because it reflects the truth of the intentions of the Islamic discourse in particular, and the discourse in general.
Keywords: الخطاب القرآني -- البلاغة العربية -- السياقات التداولية -- القرآن الكريم